Newtopia : de staat van de mensenrechten. - Gregos, Katerina; Vaneigem, Raoul; Moyn, Samuel; Khatib, Lina; Azoulay, Ariella; Sorokina, Elena; Malik, Kenan (Antwerpen : Ludion, 2012)
Agarwal, Ravi ; Baloji, Sammy ; Chernyseva, Olga ; Geers, Kendell ; Goldblatt, David ; Jaar, Alfredo ; 'T Jolle, Sven ; Svankmajer, Jan ; Warhol, Andy ; Wodiczko, Krzysztof ; et al.
Tentoonstelling 'Newtopia : de staat van de mensenrechten', Stad Mechelen, 01.09.2012 - 10.12.2012.
Nederlands
boek